Making Visible the Invisible: Reversing the Codes of Dominant Culture in Madonna's Videoclip Don't Tell Me - Oliete Pascual, Elena (Miscelánea: A Journal of English and American Studies, 2003)
In 2001, Madonna startled the public with a new image, that of the mixture of techno music with country aesthetics in the video-clip Don,t Tell Me, from her album Music. In many of her former clips, Madonna paid attention to marginal groups, bringing them to the centre. Basing my analysis on the theories of Laura Mulvey, Richard Dyer and Stuart Hall, among others, I will try to demonstrate that, in the music video Don,t Tell Me, Madonna takes the mythical figure of the cowboy as a cultural manifestation of the dominant group and relegates it to the status of 'the other', while she proposes a world of freedom in which cultural hierarchies based on gender and race issues no longer exist.
Keywords: Madonna; Video-clip; Identity; Gender; American culture